PERILAKU KONSUMEN DALAM MEMILIH PERUMAHAN PADA PERUMAHAN CIPTA LARAS BULUSULUR WONOGIRI - Sri Murwanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2009)
This study aims to analyze the relationship between consumer characteristics andproduct attributes. Dimensions of consumer characteristics, are age, education, occupation,and income consumers. While, the dimention of product atribute are price, design, facility andlocation. This research’s setting is in the property industry. The research uses chi-square as atool of analysis. The results show that there is a relationship between consumer’s characteristicsand product attribute. Education level has the highestimpact to product attribute.